Analisis Kesulitan Belajar Pada Materi Bangun Ruang Bagi Siswa Kelas 2A SD N Sampangan 2 - Maula Hanifah; Mei Fita Asri Untari; Sukamto Sukamto; Maslinda Maslinda (STKIP Andi Matappa Pangkep, 2023)
The purpose of this study was to find out the learning difficulties in geometric material and the factors that caused class 2A students at Sampangan 2 Elementary School to have difficulty understanding the geometric concept. The research method used is a qualitative research method with a descriptive approach. The subjects of this study were class 2A students at SDN Sampangan 2, which consisted of 14 male students and 14 female students. The techniques used in collecting data in this study are observation, interviews and documentation. From the research results, information was obtained that class 2A students at SDN Sampangan 2 had learning difficulties as follows: 1) class 2A students had difficulty distinguishing the various geometric shapes, 2) class 2A students had difficulty understanding the concepts of ribs, sides, corner points in a geometric shape. Following are some of the causes for class 2A students having learning difficulties; 1) the teacher only uses the lecture method so students get bored easily, 2) the teacher has not used learning media and concrete objects, 3) students do not understand basic geometric terms such as ribs, sides, points, corners.Â